(untitled) (Human Factors in Design, 2024)
Starting from the importance of stimulating children and adolescents with visual impairments in tactile, auditory sensations, and in interactions with the environment around them, this article aimed to: contact with an institution that provides visual/essential stimulation; application of Co-wear: Functional fashion co-creation method with participants, their parents and teachers; design, development and evaluation of a functional fashion collection that met participants’ design requirements. Based on applied, qualitative, exploratory research and case studies, the objectives were achieved. 8 t-shirts were developed with tactile and auditory features that favored the interactions of the participants, who tried and evaluated the clothing well.